Insulin-like growth factor-1 (IGF-1) empowering tendon regenerative therapies - Wang, Mingming; Zhang, Jiayuan; Li, Hanyue; Li, Yini; Li, Zhigang (Frontiers in Bioengineering and Biotechnology, 2025)
Tendon injury is one of the most common musculoskeletal disorders that severely affect patients’ daily lives. Unfortunately, naturally healed tendons exhibit poor quality, as they have very limited regenerative ability. Recently, therapeutic strategies involving the administration of growth factors have been advocated to enhance tendon regenerative healing. Growth factors are peptide-signaling molecules that elicit biological functions such as cell proliferation, migration, and differentiation by acting through a complex organization of cell surface receptors and activating intracellular signaling pathways. Insulin-like growth factor-1(IGF-1) represents one such factor that has shown promising effects for enhancing tendon regenerative healing in vitro and animal models. However, it is disappointing that IGF-1 has not been shown to play a very significant role in promoting tendon healing in clinical trials, which could reflect our poor understanding of the molecular mechanisms by which IGF-1 is involved in promoting tendon regenerative healing. Therefore, in this review, we summarized the roles and mechanisms of IGF-1 for enhancing tendon regenerative healing. Nevertheless, much work is still needed to optimize its effectiveness.